The Influence of Inquiry Learning Model in Improving Students' Critical Thinking Skills in View of Learning Styles in Science Learning in Elementary Schools - Oktaviani, Anna Maria; Misyanto, Misyanto; Maulana, Gilang; Jayadi, Jayadi; Utomo, Erry; Gumelar, Gumgum (EduBasic Journal: Jurnal Pendidikan Dasar, 2023)
One of the skills that students need to possess in the 21st century is the ability to think critically. Students' critical thinking skills can be developed in natural science learning. Nonetheless, not all learning models can help students improve their critical thinking skills. Undoubtedly, a suitable learning model must be chosen; the most crucial step is understanding the student's preferred learning method. This study, therefore, aims to determine the influence of the inquiry learning model in improving students' critical thinking skills in terms of various student learning styles. This study used a quantitative research approach. The method used was an experimental research method with a 2x2 factorial ANOVA experimental research type. This research was conducted in class V at eight elementary schools in Majalengka Regency, with a total sample of 262 students. The data collection instrument employed was an essay test. The data analysis techniques utilized were the normality test, homogeneity test, and the Two-Way ANOVA test using the SPSS version 25 application. The results of this study demonstrated that the critical thinking skills of students with a kinesthetic learning style had a higher average score than those with an audio-visual learning style when the teacher applied the inquiry learning model to natural science learning. It was because the activities of the inquiry learning model in science learning involved a lot of physical movement activities, which are characteristics of students with a kinesthetic learning style.